Adolescents’ possible selves, motivation and academic achievement: A literature review - Efthymiadou, Evropi; Gonida, Eleftheria N. (Psychology: the Journal of the Hellenic Psychological Society, 2024)
Possible selves are defined as the cognitive representations of future desires and fears that people have for themselves, and they are acknowledged as having motivational power. The present literature review addresses the content, factors, and importance of possible selves during adolescence, focusing on academic possible selves, which are the future images in the academic domain related to academic achievement, studies, and academic choices. Specifically, it explores the factors and procedures that facilitate the motivational power of academic possible selves and their link to positive academic outcomes, focusing on Oyserman’s identity-based motivation theory (2007, 2015). According to existing literature, the academic domain is commonly reported in adolescents’ possible selves, and academic possible selves are connected to positive development, especially for students from disadvantaged environments. However, in order academic possible selves to contribute to the academic self-regulation, they need to be linked with strategies, experienced as congruent with social identities and relevant to present actions, accompanied by motivating beliefs such as interpretation of difficulty as importance and self-efficacy beliefs, and supported by students’ social contexts. The conclusions of the review emphasize the necessity of implementing relevant interventions, especially for students living in less supportive environments. Additionally, they highlight the need for conducting relevant research and addressing implications for practice within the Greek context.